Enzymatic Hydrolysis of Pretreated Miscanthus Biomass - Olga B. Kalashnikova; Ekaterina A. Budenkova; Elena V. Ulrikh; Evgeny G. Chupakhin; Olga V. Kriger; Yakov A. Masiutin; Maria A. Smaga; Yulia S. Basova (Техника и технология пищевых производств)
Forests being mostly non-renewable, miscanthus seems to be a promising alternative energy resource. This study investigates the enzymatic hydrolysis of pretreated miscanthus biomass. The research featured Miscanthus sinensis Strictus biomass. The methods included raw material pretreatment, enzymatic hydrolysis, matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF) of monosaccharide residues, and nuclear magnetic resonance (1H NMR) spectrometry of non-hydrolyzed lignin. A hammer mill with a particle size of 0.2–0.3 mm proved to be effective for preliminary mechanical processing of miscanthus. This type of treatment provided the maximal yield of carbohydrate-containing biomass (62.33 ± 1.87%). The optimal multi-enzyme composition included Cellulase Ultra obtained from Trichoderma reeseii, xylanase obtained from Thermomyces lanuginosus, and β-gluconase obtained from Myceliophtorafergusii. The fermentation temperature was 50 ± 1°C (72 ± 1 h). At these parameters, the conversion of holocellulose of miscanthus biomass was 96.0 ± 4.8%, and the yield of reducing substances was 97.00 ± 4.85%. The article introduces the optimal enzymatic hydrolysis parameters for pretreating Miscanthus sinensis Strictus biomass as a source of carbohydrate-containing substrates and describes their subsequent use for bacterial cellulose biosynthesis. The carbohydrate composition of hydrolysates included residual lignin, such polysaccharides as glucan and xylan, and various monosaccharides, namely arabinose, xylose, galactose, glucose, and uronic acids. Hydrolyzed miscanthus proved to be an effective renewable and environmentally friendly biodiesel.